2013
DOI: 10.1136/bcr-2013-010128
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous aspergillosis due toAspergillus tamariiin an immunocompetent host

Abstract: Primary cutaneous aspergillosis is a rare disease usually caused by Aspergillus fumigatus, Aspergillus flavus, Aspergillus terreus and Aspergillus ustus. It is usually seen in immunocompromised hosts, though some cases are also reported in immunocompetent hosts. We present a case of an immunocompetent farmer who presented with generalised nodules and plaques, mimicking erythema nodosum leprosum but turned out to be cutaneous aspergillosis caused by Aspergillus tamarii. The characteristic ascospores of Aspergil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 12 publications
1
18
0
1
Order By: Relevance
“…It was difficult for clinical microbiology laboratories to identify rarely found molds as causes of various infections. The more widespread use of ITS and other gene sequencing has enabled clinical microbiology laboratories to con- fidently identify molds that are rarely found in patients after preliminary morphological examination (13)(14)(15)(16)(17)(18)29). In addition, novel fungal species associated with clinical infections have been discovered (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was difficult for clinical microbiology laboratories to identify rarely found molds as causes of various infections. The more widespread use of ITS and other gene sequencing has enabled clinical microbiology laboratories to con- fidently identify molds that are rarely found in patients after preliminary morphological examination (13)(14)(15)(16)(17)(18)29). In addition, novel fungal species associated with clinical infections have been discovered (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…These results were also in line with those of metabolic fingerprinting, in which the A. flavus, A. nomius, and A. tamarii strains were separated into three clusters based on UHPLC MS analysis. Although A. flavus, A. nomius, and A. tamarii may (Table 2) (13)(14)(15)(16)(17)(18)29). Among the 15 strains with methods of laboratory diagnosis described in detail, all of them required molecular technologies (sequencing in 14 and high-performance liquid chromatography analysis of metabolites in 1) for identification.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, several case reports have identified A. tamarii as the cause of human infections using ITS, β‐tubulin and calmodulin gene sequencing. These reports that described A. tamarii as the cause of human infections are shown in Table . The molecular biological identification at the species level would be of great importance, as the potential pathogenicity may vary between different species in the same genus.…”
Section: Discussionmentioning
confidence: 73%
“…In a case of PCA in a 65‐year‐old man, septate fungal hyphae were detected from an abscess cavity of erythematous nodular and plaque‐like lesions. The fungus isolated was finally identified as A. tamarii both phenotypically and genotypically …”
Section: Discussionmentioning
confidence: 99%
“…Case reports are issued from Somalia and India. Sharma et al 8 reported a case of an immunocompetent farmer diagnosed with cutaneous aspergillosis due to A. tamarii. To our knowledge, this case is the first A. tamarii BWI reported.…”
Section: Discussionmentioning
confidence: 99%